Extension as part of the curriculum: perspectives and experiences of business Administration students from a university in Paraná, Brazil - Oliveira, Edi Carlos de; Santos, Rejane Heloise dos; Monteiro, Maria Gabriela; Colla, Julio Ernesto (Guará Journal, 2025)
University extension, rooted in the Industrial Revolution and influenced by European and North American models, has evolved in Brazil from an assistance-based approach to a dialogical and transformative practice, consolidated by the Federal Constitution and the Law of Guidelines and Bases of Education. Extension is approached as a formative dimension that integrates teaching, research, and practical experience, strengthening ties with the community. This study analyzes how the curricularization of extension in the Administration program at the State University of Paraná, Paranavaí campus, contributes to students’ academic and professional development, based on their perspectives and experiences. Methodologically, the study adopted a qualitative, exploratory, and descriptive approach, with data collected through a focus group composed of 12 students involved in extension projects in 2024. Content analysis, based on Bardin (2011), was used to organize and interpret the emerging categories from the students’ reported experiences. The results indicate that the curricularization of extension promotes practical learning, the development of professional skills, and the expansion of knowledge, although challenges remain in the formal implementation of extension within the curriculum. Students emphasized the importance of greater protagonism in extension practices, recognizing the transformative potential of university extension in academic, civic, and social development.